The potential contribution of yellow cassava to dietary nutrient adequacy of primary-school children in Eastern Kenya; the use of linear programming - Talsma, Elise F.; Borgonjen-van den Berg, Karin J.; Melse-Boonstra, Alida; Mayer, Eva V.; Verhoef, Hans; Demir, Ayse Y.; Ferguson, Elaine L.; Kok, Frans J.; Brouwer, Inge D. (Cambridge University Press, 2018)
Introduction of biofortified cassava as school lunch can increase vitamin A intake, but may increase risk of other deficiencies due to poor nutrient profile of cassava. We assessed the potential effect of introducing a yellow cassava-based school lunch combined with additional food-based recommendations (FBR) on vitamin A and overall nutrient adequacy using Optifood (linear programming tool).